THE ROLE OF INSTAGRAM IN ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC REVIEW - Rija Arribath Dwi Daep; Nabilla Nurkhalida; Nafan Tarihoran (Adisam Publisher, 2025)
The increasing use of social media in education has brought new opportunities for language learning. This study systematically reviews the role of Instagram in enhancing English language skills. A systematic literature review (SLR) approach was employed, selecting relevant studies from reputable academic databases published between 2020 and 2024, including Mendeley, PubMed, and Taylor & Francis, with an initial identification of 921 articles. After screening for relevance and duplication, 57 studies were shortlisted, and 19 empirical studies were selected for in-depth analysis, focusing on Instagram's impact on vocabulary acquisition, writing, speaking, and student engagement. The findings indicate that Instagram positively impacts various aspects of English learning, including vocabulary acquisition, writing, speaking, and engagement. The study highlights the effectiveness of Instagram's features, such as captions, reels, and interactive tools, in fostering language development. Additionally, the research reveals that Instagram enhances motivation and self-directed learning. However, limitations such as internet accessibility and digital literacy remain challenges. The study suggests that incorporating Instagram into English language teaching (ELT) can provide an engaging and practical learning experience. Future research should explore its long-term effects and best implementation strategies in formal education settings.